EFEKTIVITAS SENAM AEROBIK LOW IMPACT TERHADAP PENURUNAN TEKANAN DARAH PADA PENDERITA HIPERTENSI DI KELURAHAN MELEBUNG - Sivia Nora Anggreini; Khairannisa Khairannisa; Isna Ovari (Ensiklopedia of Journal, 2023)
Hypertension is a condition of an abnormal increase in blood pressure and takes place continuously on several blood pressure checks to maintain normal blood pressure, hypertension occurs when the blood pressure is more than 140/90 mmHg. One of the non-pharmacological treatments for hypertension can be done with low impact aerobic exercise. The purpose of this study was to determine the effectiveness of low impact aerobic exercise on reducing blood pressure of hypertensive patients in the Melebung sub-district. This research method uses a descriptive method that uses a nursing care approach. So that there is a decrease in blood pressure after being given a low impact aerobic exercise intervention in patients with hypertension. Suggestions from low impact aerobic exercise interventions can be used as an effective way to control blood pressure in patients with hypertension.Keywords: Hypertension, Low Impact Aerobics.